Economic Evaluation of Stroke in Kano, North-Western Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The cost of in-patient care for common non-communicable diseases is enormous, considering the health financing options in most developing countries. With the general economic down-turn in the country, and the predominant out-of-pocket payment for health service method by patients in our resource challenged settings, these patients usually incur catastrophic health expenditures. However, with the recent adoption of the contributory health schemes by some state governments to reduce the out-of-pocket payment by poorly remunerated citizens, studies on the cost of illness are imperative to enhance effective provider planning and administration.Aim:To estimate the cost of illness associated with managing acute stroke in Kano.Setting and Design:We conducted a cross-sectional study where eighty five adults with established diagnosis of stroke were enrolled using a cost of illness questionnaire. Prevalence-based costs were stratified by patients’ socio-demographic characteristics and socio-economic scores (SES). The “bottomup” and “human capital” approaches were used to generate estimates of the direct and indirect costs, respectively. All estimates of the financial burden of the stroke were analyzed from the patients’ perspective using Statistical Product and Services Solutions (IBM SPSS V.22).Results:A total of 85 patients participated in the study (AKTH-45, MMSH-40). Most were within the middle-age group (69.4%), had the ischemic stroke subtype (82.4%) and belong to the low socio-economic class (41.2%). The total costs of care for the 85 patients amounted to N8,753,623.00 (21,339.37). The cost of illness for accessing care by a stroke patient was N102,983.80 (251.05). The direct cost accounted for N72,730.00 (177.40), and the indirect cost was N30,252.90 (73.75). The projected economic burden of acute stroke care by adult population in Kano was also enormous. The health facility of care, stroke subtype, and length of hospital-stay accounted for the significant difference in cost of illness between the study patients (P< 0.001).Conclusions:Cost of illness in managing acute stroke care was found to be high, and with the sizeable proportion of the population belonging to the low socio-economic class, cost-effective primary preventive strategies to reduce risks for stroke is imperative.